(untitled) (Ecological Bulletin of Kryvyi Rih District, 2021)
Ukraine’s integration into the world educational space, along with preserving the positive and effective achievements and traditions of the national model of education, aims to create new opportunities for forming their own life trajectory, the formulas for success of each individual capable of self-education, self-awareness, self-determination, self-realization and self-development. Nowadays, knowledge and education are becoming not only factors of social development, but also its foundation and the most valuable way, catalyst for the formation of modern national elite. Phenomena and trends of current human development determine the relevance of research aimed at substantiating and analyzing the prerequisites, relevance, implementation of the discipline “Basics of Ecological Terminology” in the training of ecologist based on the essence, meaning, terminological competence as part of professionalism and ecological culture of national elite. The national elite determines the intellectual, moral and ethical, political, economic climate of society and is it’s most valuable capital and priority resource. The decisive role in its preparation belongs to education, which is able to form such personal qualities that contribute to the support of a sustainable society and the fulfillment of its development with innovative elements. An integral part of professional competence, professionalism is terminological competence, which can also be considered as an independent or as a structural component of information, communication, speech, culture. The study of its essence, specifics, characteristics, levels of formation and analysis of related concepts “terminology”, “terminology system”, “term” allow to identify current problems of terminological competence in ecological science related to the level of terminological potential of the individual, ecological culture, negative aspects of modern process of term formation, problems of development of ecological terminology system. Formation of terminological competence of the ecologist — systematic, optimally organized, purposeful, provided with the use of effective teaching aids and methods and concretized by its specific principles, focused on achieving the main objectives and goals of education, improving ecological culture and strengthening the professional elite, implementation of innovative activities and implementation of ecological imperatives in the development of the country. A component of the implementation of tasks and solving problems of formation of terminological competence of future highly qualified competitive ecologists can be considered the introduction of the educational discipline “Basics of Ecological Terminology” in educational programs of higher education institutions, identification of aspects of term formation and term use, study of the dynamics of terms and the role of the latter in professional knowledge, scientific, expert, industrial, managerial, innovative activities of the ecologist.